Kajian Penggunaan LED pada Pertumbuhan Tanaman Kailan dengan Sistem Hidroponik Dalam Ruangan - Christian I G Hutapea; Leo Kalesaran; Daniel P. M. Ludong (Universitas Sam Ratulangi, 2023)
The use of LED (Light Emitting Diode) in indoor hydroponic systems can optimize the process of photosynthesis in plants. This can be a replacement of sunlight during plant growth. This study aims to examine the treatment of LED light intensity and duration of irradiation on the vegetative growth of kailan (Brassica oleracea var. alboglabra L) in indoor hydroponic systems. This experimental study consisted of 5 treatments: exposure to white (A1) and blue (A2) LED lights, exposure time of 16 hours (B1) and 20 hours (B2) and sunlight (K0) as a control in a greenhouse. Treatment with LED lights placed in the growth chamber. Treatment consisted of 4 replicates with a total of 20 plants. The results showed that the white LED light intensity and 20 hours of irradiation time were better than other treatments including plant height, stem diameter, leaf width, leaf length, number of leaves, fresh weight, root weight and water efficiency.